The effect of creatine loading on body mass and vertical jump in female athletes - Miszko, T. A.; Baer, J. T.; Vanderburgh, P. M (Medicine & Science in Sports & Exercise, 1998)
Division I female softball players (N = 14) were divided into a 25 g/d lactose placebo and a 25 g/day creatine monohydrate 6-days supplementation group. Pre and post measures of body composition, vertical reach, and vertical jump were made. An cycle-ergometer test that measured repeated anaerobic sprints was also performed. There were no significant differences within or between groups for caloric intake, skinfold measures, lactate, or vertical jump. Within each group body mass increased significantly.Implication. Creatine supplementation over six days did not improve vertical jump performance or other measures in these athletic young women.